An age-structured within-host HIV model with T-cell competition. (December 2017) - Wang, Yan; Liu, Kaihui; Lou, Yijun
Abstract: Recent studies demonstrate that resource competition is an essential component of T-cell proliferation in HIV progression, which can contribute instructively to the disease development. In this paper, we formulate an age-structured within-host HIV model, in the form of a hyperbolic partial differential equation (PDE) for infected target cells coupled with two ordinary differential equations for uninfected T-cells and the virions, to explore the effects of both the T-cell competition and viral shedding variations on the viral dynamics. The basic reproduction number is derived for a general viral production rate which determines the local stability of the infection-free equilibrium. Two special forms of viral production rates, which are extensively investigated in previous literature, the delayed exponential distribution and a step function rate, are further investigated, where the original system can be reduced into systems of delay differential equations. It is confirmed that there exists a unique positive equilibrium for two special viral production rates when the basic reproduction number is greater than one. However, the model exhibits the phenomenon of backward bifurcation, where two positive steady states coexist with the infection-free equilibrium when the basic reproduction number is less than one. Highlights: The effects of viral shedding and T-cell competition are studied via a hybrid model. The well-posedness of the model is rigorously verified. Local stability of the infection-free equilibrium in terms of R 0 is investigated. Two special forms of viral production rates are investigated. Reduced DDE models based on two special forms exhibit backward bifurcation.